Crashing Waves Activity - Foss, Louisa L (Treating Those with Mental Disorders: A Comprehensive Approach to Case Conceptualization and Treatment, 2014)
Note: This is the bound book only and does not include access to the Enhanced Pearson eText. To order the Enhanced Pearson eText packaged with a bound book, use ISBN 0133834255.Treating Those with Mental Disorders: A Comprehensive Approach to Case Conceptualization and Treatment is the authoritative reference on selecting and applying treatments for use in counseling and treating those with mental disorders. In it, students and new counselors don’t just learn about the clinical issues, the DSM-5 system of diagnosis, and interventions that can be used in counseling and treating those with mental disorders, they see clearly how to proceed in treatment planning and how to implement treatment approaches and interventions. The authors present a conceptual framework model, I CAN START, which consists of case conceptualization components and addresses treatment planning from a strength-based, contextually sensitive perspective. Case studies; creative Clinical Toolboxes; Voices from the Trenches; a comfortable presentation of the material; and a comprehensive, rigorous assimilation of the current treatment literature combine to empower counselors to thoughtfully and deliberately help their clients tackle their complex issues and difficulties. The Enhanced Pearson eText features Case studies, creative Clinical Toolboxes, and Voices from the Trenches which present real-life examples of critical counseling concepts and approaches.Improve mastery and retention with the Enhanced Pearson eText* The Enhanced Pearson eText provides a rich, interactive learning environment designed to improve student mastery of content. The Enhanced Pearson eText is:Engaging. The new interactive, multimedia learning features were developed by the authors and other subject-matter experts to deepen and enrich the learning experience. Convenient. Enjoy instant online access from your computer or download the Pearson eText App to read on or offline on your iPad® and Android® tablet.* Affordable. The Enhanced Pearson eText may be purchased stand-alone or with a loose-leaf version of the text for 40-65% less than a print bound book. *The Enhanced eText features are only available in the Pearson eText format. They are not available in third-party eTexts or downloads.*The Pearson eText App is available on Google Play and in the App Store. It requires Android OS 3.1-4, a 7” or 10” tablet, or iPad iOS 5.0 or later.
Keywords: dept.csp

New counselors' experiences of community health centers - Freadling, A.H.; Foss-Kelly, L.L. (Counselor Education and Supervision, 2014)
This phenomenological study explored 6 new counselors' experiences working in community mental health centers and their experiences of the Council for Accreditation of Counseling and Related Educational Programs-accredited training received in preparation for such work. Three themes from the interviews were identified to provide implications for counselor preparation: contextual descriptions, essential graduate training components, and supportive factors. © 2014 by the American Counseling Association. All rights reserved.
Keywords: community mental health; counselor education; dept.csp